Pemetaan Geospasial Panti Sosial di Kota Kendari Berbasis Sistem Informasi Geografis (SIG) - Mashaf, Salsabila; Fadillah, Nur; Wulandari, Suci; Naisyarah, Wifna; Nangi, Jumadil (Jurnal Sains dan Teknologi (JSIT), 2025)
The city of Kendari is home to various social institutions such as orphanages and nursing homes that require support fromthe community and attention from the government. However, limited information regarding the locations and supportingdata of these social institutions often poses challenges in the distribution of aid and the formulation of social policydecisions. This study aims to develop a web-based Geographic Information System (GIS) that visually and informativelymaps the distribution of social institutions in Kendari. The methods employed include literature review, needs analysis,system design, implementation, and testing. The system is developed using PHP for the backend, Leaflet.js for interactivemap visualization, and MySQL as the database. The data used consist of spatial data in the form of geographiccoordinates and non-spatial data such as institution names, categories, addresses, contact details, and social mediaaccounts. The testing technique applied is black box testing to evaluate key system functionalities, including map display,location search, data management by administrators, and interface reliability. The results show that the systemsuccessfully displays an interactive digital map with informative location icons and supports data operations such as add,edit, and delete through an admin interface. This system is expected to serve as an effective information tool for the public,volunteers, and authorities in accessing and managing social institution data efficiently and transparently.